Multimedia Whiteboard Animation Untuk Meningkatkan Kemampuan Problem Solving Pada Guru - Dian Wahyuningsih; Suyatiningsih (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2020)
This study aims to develop whiteboard animation multimedia to improve teachers’ problem-solving skills. The development used the Borg and Gall model with a qualitative descriptive approach. The subjects of this research were teachers in the Special Region of Yogyakarta (DIY). The product developed has been rated by subject matter experts and media experts. Three stages of the trial have been carried out, including the initial field test reached 74.8%, the main field test with reached 86.5%, and an operational test reached 83.5%. The product implementation result proved that multimedia increased by 41%. The questionnaire showed that the material presented was easy to practice. From the data, it can be concluded that whiteboard animation multimedia that have the good qualification to improve teachers problem-solving skill.